Effect of Dispersed Density and Pre-treatment on Rehydration of Dried Spinach Leaves - GARG, S K; LOHANI, U C (Journal of Agricultural Engineering, 2012)
Drying behaviour of spinach leaves was characterized for three levels of temperature (50, 60 and 70ÂºC), two levels of pretreatment (blanched and unblanched) and two levels of dispersed density (30 kg.m-3 and 50 kg.m-3) at a constant air velocity of 1.6 m.s-1. The rehydration and optical density values were optimized for blanched leaves at 70Â°C temperature and 50 kg.m-3 dispersed density. Rehydration and optical density values varied from 212.66 to 256.58 and 0.43 to 0.67, respectively, with increase in temperature.